2004
DOI: 10.1088/0960-1317/15/1/020
|View full text |Cite
|
Sign up to set email alerts
|

Scum-free patterning of SU-8 resist for electroforming applications

Abstract: A simple approach is developed to obtain scum-free pattern transfer in SU-8 resist by UV-lithography for electroforming applications. SU-8 is an epoxy-based negative resist used in the fabrication of high-aspect ratio microstructures. SU-8 resist poses considerable processing difficulties and tends to leave organic residues of undeveloped resist on the surface of the exposed metallic seed layer. Scum-free pattern transfer in SU-8 resist is important for the subsequent electroplating process used to fabricate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 16 publications
2
12
1
Order By: Relevance
“…1(b and c). However, some roughness and waviness of the sidewall are still found, possibly caused by the use of film mask for exposure (Agarwal et al, 2005). In any case, it is important that one should remove any residual resist layer with no stiction, before attempting electroforming; otherwise, the flatness of the surface would be affected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1(b and c). However, some roughness and waviness of the sidewall are still found, possibly caused by the use of film mask for exposure (Agarwal et al, 2005). In any case, it is important that one should remove any residual resist layer with no stiction, before attempting electroforming; otherwise, the flatness of the surface would be affected.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, SU-8 can be also used as an electroplating mould in many applications (Agarwal et al, 2005). The present study aims to develop a copper www.elsevier.com/locate/micron Micron 39 (2008) 263-268 electroforming process by patterning SU-8 negative resist using a deep UV lithography technique to fabricate PEM fuel cell stack bipolar plates.…”
Section: Introductionmentioning
confidence: 99%
“…The stress-strain data for a nominal UV cure time of 30 s was used throughout the modeling process. The polymer replication is assumed to have taken place within a rigid nickel mold of the kind that can be fabricated with micromachining and nickel electroforming methods (Agarwal et al 2005).…”
Section: Finite Element Modelingmentioning
confidence: 99%
“…Earlier some authors (Agarwal et al 2005;Shew et al 2003) had reported the surface roughness of SU-8 microstructures using X-ray lithography to be around 10 nm root mean square (rms), however, no detailed studies were reported that also consider the depth dependent roughness. Accordingly, we undertook detailed theoretical and experimental studies to study the dependence of surface roughness on the incident beam spectrum, along and perpendicular to the direction of beam and on the depth of the resist (Vora et al 2006).…”
Section: Surface Roughnessmentioning
confidence: 99%